Clostridium difficile presence in Spanish and Belgian hospitals. (November 2016) - Rodriguez, C.; Fernandez, J.; Van Broeck, J.; Taminiau, B.; Avesani, V.; Boga, J.A.; Vazquez, F.; Delmée, M.; Daube, G.
Abstract: Clostridium difficile is recognised worldwide as the main cause of infectious bacterial antibiotic-associated diarrhoea in hospitals and other healthcare settings. The aim of this study was to first survey C. difficile prevalence during the summer of 2014 at the Central University Hospital of Asturias (Spain). By typing the isolates obtained, it was then possible to compare the ribotype distribution at the Spanish hospital with results from the St Luc University Hospital in Belgium over the same period. The prevalence of positive cases reported in Spain and Belgium was 12.3% and 9.3% respectively. The main PCR-ribotypes previously described in Europe were found in both hospitals, including 078, 014, 012, 020 and 002. In the Spanish hospital, most of the C. difficile -positive samples were referred from oncology, acute care and general medicine services. In the Belgian hospital the majority of positive samples were referred from the paediatric service. However, a high percentage of isolates from this service were non-toxigenic. This study finds that the presence and detection of C. difficile in paediatric and oncology services requires further investigation. Highlights: C. difficile prevalence was investigated in two European hospitals. The most common PCR-ribotypes reported in Europe were found in both hospitals. The variety of PCR-ribotypes detected suggests there is neither regional infection nor contamination within the hospital. Paediatric service had a high number of non-toxigenic strains. A great part of positive samples were referred from oncology.